The principals' Co-curricular Activities Managerial Strategies for the Devlopment of Etudents' Knowledge in Unity Schools, North Central, Nigeria - Oke, E. B.; O0DO , Ichima Michael (International Journal of Educational Management, 2025)
The study examined the principals' co-curricular activities managerial strategies for developing students' knowledge in unity schools, North Central Nigeria. Descriptive survey design was adopted for this study. The total population for the study was 2,701 teachers and 4,356 Senior Secondary (SS) 3 students, 2018/2019 academic session. The sample size for this study comprised of 320 teachers and 338 students. Multistage sampling procedure was used for this study. Four out of seven states were randomly selected and each state was treated as a strata. Proportionate sampling technique and purposive sampling technique were used in the selection of students and teachers respectively. The questionnaire title principals' co-curricular activities managerial strategies for developing students' knowledge in unity schools, North Central Nigeria, was administered to the respondents after validation by experts in the Department of Education Foundation, Faculty of Education, University of Abuja, Nigeria. Cronbach Alpha was used to find the degree of internal consistency and a value (r=0.84) was obtained. The analysis of data collected from the respondents was done using mean scores and standard deviation. The findings revealed the managerial strategies adopted by the principal in ensuring quality co-curricular activities delivery in the unity schools. These are; systematic planning, adequate supervision. effective organization and sustainable evaluation. The findings of the study showed that co-curricular activity is an instrument for developing students' knowledge. These are critical and analytical thinking, reading and listening ability, professional knowledge among others. The study recommended among others the creation of office of the vice principal, co-curricular activities for effective management of co-curricular activities in unity schools, North Central Nigeria.